(untitled) (Computer systems and information technologies, 2022)
Evidence of the complexity of the cybersecurity problem is the rapid increase in the number of information security breaches and losses on cybersecurity threats combined with an increase in the average loss from each of the breaches. Therefore, it is necessary to create requirements for a cybersecurity system that could provide more opportunities in the choice of methods in the management of the protection of automated information systems. The task of determining the optimal quality indicators of information resource management systems of automated systems is one of the most important problems in designing integrated information security systems. This is due to the complexity of such systems, the presence of many variable parameters, and the complexity of calculating quality indicators. In addition, the determined quality indicators should not only ensure the optimality of the target function, but also the stability of the protection system in a wide range of external adverse effects. The problem is that the existing methods of calculating integrated quadratic estimates (IQE) do not take into account errors in determining quality indicators, as well as the vector nature of these indicators. The aim of this work is to solve problems (development of algorithms), which are a problem of optimization of stable protection management systems using vector objective functions. Based on the model of information management system protection of information resources in the form of an automatic control system, the method of forming integrated quadratic estimates (IQE) of control error is proposed. This method takes into account the weights of the estimates at the desired installation time and standard transfer functions. Algorithms for calculating IQE according to the modified Katz formula and Ostrom’s method for arbitrary order control systems are developed, including vector representation of the objective function of the protection system. The vector penalty function is proposed and the algorithm of its calculation is developed to display the degree of infringement of conditions of stability of parameters of the system of protection by the Rauss-Hurwitz criterion.